Effects of Synthetic Acaricides and Nosema ceranae (Microsporidia: Nosematidae) on Molecules Associated with Chemical Communication and Recognition in Honey Bees - Porrini, Martín Pablo (2020)
Acaricides and the gut parasite Nosema ceranae are commonly present in most productive hives. Those stressors could be affecting key semiochemicals, which act as homeostasis regulators in Apis mellifera colonies, such as cuticular hydrocarbons (CHC) involved in social recognition and ethyl oleate (EO) which plays a role as primer pheromone in honey bees. Here we test the effect of amitraz, coumaphos, tau-fluvalinate and flumethrin, commonly applied to treat varroosis, on honey bee survival time, rate of food consumption, CHC profiles and EO production on N. ceranae-infected and non-infected honey bees. Di erent sublethal concentrations of amitraz, coumaphos, tau-fluvalinate and flumethrin were administered chronically in a syrup-based diet. After treatment, purified hole-body extracts were analyzed by gas chromatography coupled to mass spectrometry. While N. ceranae infection was also shown to decrease EO production affecting survival rates, acaricides showed no significant effect on this pheromone. As for the CHC, we found no changes in relation to the health status or consumption of acaricides. This absence of alteration in EO or CHC as response to acaricides ingestion or in combination with N. ceranae, suggests that worker honey bees exposed to those highly ubiquitous drugs are hardly differentiated by nest-mates. Having determined a synergic effect on mortality in worker bees exposed to coumaphos and Nosema infection but also, alterations in EO production as a response to N. ceranae infection it is an interesting clue to deeper understand the e ects of parasite-host-pesticide interaction on colony functioning.